An inherently infinite-dimensional quantum correlation - Andrea Coladangelo (Nature Portfolio, 2020)
The existence of nonlocal correlations which cannot be attained exactly by finite-dimensional systems, but can be attained by infinite-dimensional ones, has been the subject of several theoretical efforts. Here, Coladangelo and Stark exhibit such a correlation, in a form that requires only two players.